(Why) have women left East Germany more frequently than men? - Stauder, Johannes (Heidelberger Jahrbücher online, 2018)
There has been a massive internal migration from East to West Germany after German reunification in 1990. While there is a higher net emigration rate for women than for men, this is not the result of a surplus of women leaving East Germany, but a result of less West German women migrating to East Germany. Only at ages under 25, some more women than men migrated from East to West Germany. Using the German Socio-Economic Panel, this paper describes gender specific internal migration from East to West Germany and from West to East Germany between 1991 and 2012. It separates migration for labour market reasons, migration for educational reasons and migration due to a partner. In addition, the description differentiates original migration vs. re-migration and highly educated vs. lowly educated women and men. Results show that a new job in the respective other part of Germany is the most frequent reason for internal migration in both directions. However, the gender differences in East-West-migration with more (young) women moving West do not mainly result from job-related moves, but from migration with educational motives. In a similar way, the excess number of men over women who moved from West to East Germany is mainly the result of educational migration. These findings contradict speculations about a stronger discrimination of women on the Eastern compared to the Western labour market.